PD-L1 score as a prognostic biomarker in asian early-stage epidermal growth factor receptor-mutated lung cancer. (January 2023) - Saw, Stephanie P.L.; Ng, Win Pin; Zhou, Siqin; Lai, Gillianne G.Y.; Tan, Aaron C.; Ang, Mei-Kim; Lim, Wan-Teck; Kanesvaran, Ravindran; Ng, Quan Sing; Jain, Amit; Tan, Wan Ling; Rajasekaran, Tanujaa; et al.
Abstract: Aim: To determine the prognostic value of programmed death-ligand 1 (PD-L1) score in early-stage epidermal growth factor receptor ( EGFR )-mutated non-small cell lung cancer (NSCLC), contrasted against EGFR- wildtype NSCLC. Methods: Consecutive patients with Stage IA-IIIA NSCLC diagnosed 1st January 2010–31st December 2019 at National Cancer Centre Singapore with evaluable EGFR and PD-L1 status were included. Co-primary end-points were 2-year disease-free survival (DFS) and 5-year overall survival (OS) by Kaplan–Meier method. Results: 455 patients were included (267 EGFR-mutated, EGFR-M+; 188 EGFR-wildtype, wt). Median age at diagnosis was 65 years, 52.3% (238/455) of patients were males, 62.9% (286/455) of patients were never-smokers and 92.5% (421/455) of patients had R0 resection. Stage IA comprised 42.4% (193/455) of patients, Stage IB comprised 23.1% (105/455) of patients, Stage IIA comprised 10.8% of patients (49/455), Stage IIB comprised 5.1% of patients (23/455) and Stage IIIA comprised 18.7% (85/455) of patients. Among EGFR-M+, 45.3% (121/267) were Ex19del and 41.9% (112/267) were L858R. PD-L1 ≥1% among EGFR-M+ and EGFR-wt was 45.3% (121/267) and 54.8% (103/188) respectively (p = 0.047). At median follow-up of 47 months, 178 patients had relapsed. Among EGFR-M+, 2-year DFS comparing PD-L1 <1% and PD-L1 ≥1% was 78.1% and 67.6% (p = 0.007) while 5-year OS was 59.5% and 42.8% (p = 0.001), respectively. Controlling for age, gender, lymphovascular invasion, adjuvant therapy and resection margin status, PD-L1 ≥1% (hazard ratio, HR 2.18, 95% CI 1.04–4.54, p = 0.038), stage IIB (HR 7.78, 95% CI 1.72–35.27, p = 0.008) and stage IIIA (HR 4.45, 95% CI 1.44–13.80, p = 0.01) emerged as independent predictors of inferior OS on multivariable analysis. In exploratory analysis, genomic analysis of 81 EGFR-M+ tumours was performed. PD-L1 ≥1% tumours had significantly higher rates of TP53 mutations (36.1% versus 15.6%, p = 0.04), with predominantly missense mutations. Conclusion: PD-L1 ≥1% is an independent predictor of worse OS among early-stage EGFR-mutated NSCLC and is associated with inferior DFS regardless of EGFR status. PD-L1 score as a risk stratification factor should be evaluated in prospective adjuvant studies among EGFR-mutated NSCLC. Highlights: PD-L1 ≥1% is an independent predictor of worse overall survival in resected epidermal growth factor receptor ( EGFR )-mutated non-small cell lung cancer (NSCLC). PD-L1 ≥1% is significantly associated with worse disease-free survival regardless of EGFR status. TP53 co-mutations are more common among PD-L1 ≥1% EGFR -mutated NSCLC. PD-L1 should be a stratification factor in adjuvant trials for EGFR -mutated NSCLC.